(untitled) (Economic and Political Thought, 2018)
The article discusses the use of export insurance backed by the State Treasury as a recognized credit risk mitigation technique under Regulation 575/2013, concerning the exposure to risk of export credit offered by the banking sector. Recognition of the insurance policy of KUKE SA [Export Credit Insurance Corporation], a Polish ECA, as such a technique is one of the conditions for appropriate determination of the risk weight for the estimation of the capital adequacy ratio of the bank. The issue is of great importance for higher engagement of the domestic banking sector in providing export credits and supporting the domestic companies entering foreign markets by increased involvement in financing companies importing products and services from Poland. In order to illustrate the issues in more detail, the article also analyses main international regulations requirements that need to be taken into account in the context of subsidizing export activity as well as main principles of the officially supported export credits with special focus on the compliance of unfunded credit protection provided by KUKE SA with CRR. The article does not deal with the issue referred to in Article 194 par. 5 in conjunction with Article 201 par. 1 Capital Requirements Regulation concerning the official provider of unfunded credit protection and requirements that a provider of unfunded credit protection should fulfil to be a recognised one. The analysis of the above issue will be discussed in a separate article. Attention must be also drawn to the fact that the considerations presented in the article concern only an insurance policy and not insurance collateral applied in foreign trade for the needs of the protection of payment by foreign trade partners in short-term transactions, which will also be discussed in a separate article.